Influence of oral magnesium supplementation on cardiac events among survivors of an acute myocardial infarction. Issue 6904 (4th September 1993) - Galløe, A M; Rasmussen, H S; Jørgensen, L N; Aurup, P; Balsløv, S; Cintin, C; Graudal, N; McNair, P
Abstract : OBJECTIVE--To investigate the effect of long term oral magnesium treatment on incidence of cardiac events among survivors of an acute myocardial infarction. DESIGN--Double blind, placebo controlled parallel study in which patients were randomised to treatment or placebo. SETTING--Two coronary care units and corresponding outpatient clinics. SUBJECTS--468 survivors of an acute myocardial infarction (289 men and 178 women) aged 31-92. INTERVENTIONS--One tablet of 15 mmol magnesium hydroxide or placebo daily for one year. MAIN OUTCOME MEASURES--Incidences of reinfarction, sudden death, and coronary artery bypass grafting in one year. RESULTS--There was no significant difference between treatment and placebo groups in the incidence of each of the three cardiac events, but when the events were combined and drop outs were excluded from calculations there was a significantly higher incidence of events in the treatment group (56/167 v 33/153; relative risk 1.55 (95% confidence interval 1.07 to 2.25); p = 0.02). When the timing of events was incorporated by means of a Kaplan-Meier plot the treatment group showed a significantly higher incidence of events whether drop outs were included or excluded (p < 0.025). CONCLUSION--Long term oral treatment with 15 mmol magnesium daily doses not reduce the incidence of cardiac events in survivors of an acute myocardial infarction and, indeed, seems to increase the risk of developing a cardiac event. Consequently, this treatment cannot be recommended as secondary prophylaxis for such patients.